Effectiveness of an antioxidant-rich diet on childhood asthma outcomes: A randomized controlled trial - Theerapan Songnuy; Putrada Ninla‐aesong; Piyada Thairach; Janjira Thok-Ngaen (BMC Nutrition, 2025)
BACKGROUND: Oxidative stress contributes to the initiation of inflammatory processes in the airway passages of asthmatic patients. An antioxidant-rich diet may alleviate asthmatic outcomes; however, evidence for this is currently scant. Hence, we aimed to assess whether an antioxidant-rich diet with usual asthma care can improve clinical outcomes and pulmonary function. METHODS: We enrolled mild to moderate asthmatic children who were being treated at two primary care settings in southern Thailand from October5, 2021 to May11, 2022. Participants were randomly assigned into a control group (n = 33) that received usual asthma care and an experimental group (n = 48) that received tomato juice and mixed fruit juice along with usual care for an 8-week period. Questionnaire, Inhaled Corticosteroids (ICS) dose usage, Asthma Control Test (ACT), Pediatric Asthma Quality of Life Questionnaire (PAQLQ), Pulmonary Function Test (PFT) and serum antioxidant levels (lycopene, beta-carotene and ascorbic acid) were compared for the 1st and 2nd visits. RESULTS: A total of 80 participants completed the study with one control group participant lost in the follow up. Compared with the control group, the experimental group showed significant improvement in ACT scores (1.083 v.-0.786; p-value, 0.005) and PAQLQ total scores (2.208 v. -4.250; p-value, 0.002). In addition, serum beta-carotene increased in an experimental group after the 8-week duration (0.706 v. 0.783; p-value, 0.006) but not significantly changed in mean difference when compared with the control group (p-value, 0.879). However, ICS dose usage, PFT, and serum lycopene or ascorbic acid levels did not show significant differences over the 8-week study. Good compliance and low side effects regarding the fruit juice consumption were observed among participants. CONCLUSIONS: The antioxidant-rich diet supplementation with usual care in asthmatic children may improve asthma control, quality of life and serum beta-carotene level. Nevertheless, the intervention did not change ICS dose usage, PFT or other serum antioxidant levels. With favorable palatability and low undesirable effects, tomato juice and mixed fruit juice may be used as an adjuvant therapy to the regular childhood asthma care. The results suggest that for further investigation, a larger sample size and long-term multi-center trial are warranted. TRIAL REGISTRATION: The clinical trial described in this paper was retrospectively registered on 29 May 2023 at The Thai Clinical Trials Registry under the registration number (ID: TCTR 20230529001).
Keywords: Asthma and respiratory diseases; Vitamin C and Antioxidants Research; Antioxidant Activity and Oxidative Stress